Effectiveness of Medical-dental Coordinated Care for Diabetes Patients With Periodontal Disease at Selected Public Primary Care Clinics, in Kuantan, Pahang - Tim, Myo Han (2018)
In Malaysia, prevalence of diabetes mellitus (DM) has increased almost a two-fold from 11.6% in 2006 to 22.6% in 2013 and among them only 20 % achieved treatment target of HbA1c <6.5%) while healthy periodontal tissues in all age groups decreased from 9.8% in 2000 to 3.2% in 2010 with increasing severe complicated periodontal disease (PD)cases. Medical-dental coordinated care is recommended under the light of bidirectional relationship between DM and PD and effect of periodontal treatment (PT) on glycemic control of DM patients. However, PD assessment and taking treatment for it have been still overlooked by both DM patients themselves and medical professionals. Besides, evidences on effectiveness of medical-dental coordinated care to DM patients with periodontitis from public primary care clinics (PPCCs) and administrative issues to implement it have been still limited. This clinical management intervention study aimed to evaluate the effectiveness of medical-dental coordinated care to DM patients with periodontitis including constraints to implement it. Screening PD among DM patient at diabetic clinics of 3 PPCCs, referring DM patients with periodontitis to PD specialists’ clinics, providing standard-DM care and periodontal treatment (PT), sharing glycemic control and PD-status information, tracing defaulters and encouraging for regular DM follow-up and taking PT completely by the medical team and PD specialists were included in the medical-dental coordinated care. Out of 239 DM patients who were screened PD by basic periodontal examination (BPE), 52% (123/239) had periodontitis. Out of 123 DM patients with periodontitis, 44 % (54/123) agreed to seek PT and referred them to two PD specialists’ clinics. However, 71% (38/54) took PT and 27% (16/54) declined to PT appointment offered by PD specialists’ clinics. Out of 38 patients, 97.4%(37/38) patients adhered to DM care while only 44.7% (17/38) patients completed PT because of having inconvenience to take PT. Achievement of target glycemic control HbA1c ≤ 6.5% of the cases who completed PT was significantly highest comparing with that of the positive controls who did not complete PT and the negative controls who did not take PT (47.1% vs 15.8% vs 15.2%). Clinical resolution of periodontitis in PPD significantly reduced after taking PT -probing periodontal depth 3.34 mm (before) vs 2.63 mm (after). Number needed to treat (95%CI) and standardized mean difference of taking PT on achieving glycemic control target in HbA1c were 4.9 (1.3-19.1), and -0.52 respectively. Thus, the medical-dental coordinated care should be provided to DM patients with periodontitis to assist in reducing of DM patients who did not achieve their HbA1c target. A further study should be conducted to explore the inconveniences of the patients to seek PT. (Abstract by Author)